Children with migraine: Provocation of headache via pressure to myofascial trigger points in the trapezius muscle? – A prospective controlled observational study. (26th September 2017) - Landgraf, M.N.; Biebl, J.T.; Langhagen, T.; Hannibal, I.; Eggert, T.; Vill, K.; Gerstl, L.; Albers, L.; von Kries, R.; Straube, A.; Heinen, F.
Abstract: Background: The objective was to evaluate a supposed clinical interdependency of myofascial trigger points and migraine in children. Such interdependency would support an interaction of spinal and trigeminal afferences in the trigemino‐cervical complex as a contributing factor in migraine. Methods: Children ≤18 years with the confirmed diagnosis of migraine were prospectively investigated. Comprehensive data on medical history, clinical neurological and psychological status were gathered. Trigger points in the trapezius muscle were identified by palpation and the threshold of pressure pain at these points was measured. Manual pressure was applied to the trigger points, and the occurrence and duration of induced headache were recorded. At a second consultation (4 weeks after the first), manual pressure with the detected pressure threshold was applied to non‐trigger points within the same trapezius muscle (control). Headache and related parameters were again recorded and compared to the results of the first consultation. Results: A total of 13 girls and 13 boys with migraine and a median age of 14.5 (Range 6.3–17.8) years took part in the study. Manual pressure to trigger points in the trapezius muscle led to lasting headache after termination of the manual pressure in 13 patients while no patient experienced headache when manual pressure was applied to non‐trigger points at the control visit ( p  < 0.001). Headache was induced significantly more often in children ≥12 years and those with internalizing behavioural disorder. Conclusion: We found an association between trapezius muscle myofascial trigger points and migraine, which might underline the concept of the trigemino‐cervical complex, especially in adolescents. Significance: In children with migraine headache can often be induced by pressure to myofascial trigger points, but not by pressure to non‐trigger points in the trapezius muscle. This supports the hypothesis of a trigemino‐cervical‐complex in the pathophysiology of migraine, which might have implications for innovative therapies in children with migraine.